Birth defects associated with obesity - Ovadya Rosenbluh; Asnat Walfisch (IMR Press, 2021)
Background: In women of reproductive age, obesity is the most common medical condition. A condition which is increasing in prevalence worldwide. Obesity during pregnancy could have both short- and long-term adverse consequences for both mother and child. Methods: In this narrative review we discuss the most prominent observational studies and meta-analyses focusing on the association between maternal obesity (and BMI) and fetal congenital anomalies. Possible pathophysiological pathways linking the two are also discussed. Results: Obese women were found to have an increased at-birth prevalence of a wide range of fetal anomalies. These include congenital heart anomalies and neural tube defects, with a possible "dose-response" correlation. The reasons for that may include increased insulin resistance in early pregnancy and nutritional deficiencies, but also probably result from the challenges of fetal anomaly detection during a detailed ultrasound in obese women. Discussion: A large array of different fetal anomalies have been found to be increased in the maternal obese population. The incidence of fetal neural tube defects and serious heart anomalies among the obese population might grow by 30%. Congenital anomalies are known to be a major cause of stillbirth and infant mortality, and are important contributors to preterm delivery and childhood morbidity. The possible dose response pattern observed between the severity of obesity and teratogenic potential necessitates further investigation, which may also shed light on the underlying pathophysiology. The increasing prevalence of obesity in general and particularly in the pregnant population may thus have serious health implications. Education regarding the many risks associated with obesity, for mothers and their babies, are warranted.